2019
DOI: 10.1111/aos.14184
|View full text |Cite
|
Sign up to set email alerts
|

Task shifting of intraocular injections from physicians to nurses: a randomized single‐masked noninferiority study

Abstract: Purpose To test if task shifting of intraocular injections to nurses in a real‐world setting can result in similar visual function outcome with equal safety profile. Method All patients with either age‐related macular degeneration, retinal vein occlusion or diabetic macular oedema remitted to intraocular injections at a tertiary ophthalmology department in Norway between March 2015 and May 2017, were asked to participate. The participants were randomized to either nurse‐ or physician‐administered intraocular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…Conducting interviews came from a desire to learn from the trained nurses because an interview can give in-depth information on participants’ attitudes, thoughts, and actions [ 37 ]. This qualitative study is an important supplement to our previous RCT [ 10 ]. This mixing of methods can act complementarily and provide a richer and deeper understanding of the task shift concept [ 38 ], and it is in line with recommendations for training needs assessment [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conducting interviews came from a desire to learn from the trained nurses because an interview can give in-depth information on participants’ attitudes, thoughts, and actions [ 37 ]. This qualitative study is an important supplement to our previous RCT [ 10 ]. This mixing of methods can act complementarily and provide a richer and deeper understanding of the task shift concept [ 38 ], and it is in line with recommendations for training needs assessment [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, with the first randomized controlled study, we were able to show that nurse-administered injections are just as safe and have the same positive effect as injections given by physicians [ 10 ]. Based on these results, we established a nurse-driven injection clinic at the University Hospital in Trondheim, Norway.…”
Section: Introductionmentioning
confidence: 99%
“…After the first publication of nurse-led IVI by Varma and colleagues in 2013, many similar reports have emerged constantly. Most of them were from European countries, such as UK,[ 8 35 36 40 41 42 43 44 ] Denmark,[ 45 ] Norway,[ 46 47 ] and Spain[ 44 ]; a few were from countries outside Europe, such as New Zealand[ 48 ] and Singapore. [ 49 50 ] Table 2 demonstrates a summary of the literature review of studies related to nurse-led IVI.…”
Section: Capacity Building In Dr Screeningmentioning
confidence: 99%
“…[ 8 45 48 ] In addition, for qualitative evaluation, the majority of patients reported satisfaction with the nurse-led IVI service, based on the positive outcomes from the questionnaire. [ 35 41 43 44 47 49 ] Bolme and colleagues conducted a randomized single-masked noninferiority study of IVI rendered by nurses and ophthalmologists in Norway; they concluded that the task shifting of IVI to nurses can be performed without increased risk to damage to visual function. Sixty percent of patients did not know whether it was a physician or a nurse who performed the injection.…”
Section: Capacity Building In Dr Screeningmentioning
confidence: 99%
“…The safety profile of nurse practitioners delivering an intravitreal anti-VEGF injection service has been well established [1,2]. In most eye units across the UK, nurses are exclusively providing the intravitreal anti-VEGF injection services [3], whereas others adopt a mixed model consisting of nurses and doctors.…”
Section: Introductionmentioning
confidence: 99%